Too Afraid to Learn: Attitudes towards Statistics as a Barrier to Learning Statistics and to Acquiring Quantitative Skills. (24th December 2013) - Slootmaeckers, Koen; Kerremans, Bart; Adriaensen, Johan
<x xml:space="preserve">Abstract</x> Quantitative skills are important for studying and understanding social reality. Political science students, however, experience difficulties in acquiring and retaining such skills. Fear of statistics has often been listed among the major causes for this problem. This study aims at understanding the underlying factors for this anxiety and proposes a potential remedy. More specifically, we advocate the integration of quantitative material into non‐methodological courses. After assessing the influence of dispositional, course‐related and person‐related factors on the attitudes towards statistics among political science students, we provide insights into the relation between these attitudes on the one hand and the learning and retention of statistics skills on the other. Our results indicate that a curriculum‐wide approach to normalise the use of quantitative methods can not only foster interest in statistics but also foster retention of the acquired skills.